Direct Translation Procedures in Children Billingual Story Book of Bonnie dan Perayaan - Nisa Nuranisa (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2019)
This research tries to find out a direct translation procedures of a bilingual children story book entitled Bonnie dan Perayaan. This research is a qualitative research. The source of data is the bilingual book entitled Bonnie dan Perayaan that contains of 23 pages. The result shows that literal translation is the most dominant direct translation procedure used in bilingual children storybook Bonnie dan Perayaan. There are 76.2% translated with literal procedure, and 23.8% translated with borrowing procedure. Literal translation becomes the most dominan number because this makes the TL version has closest structure and style as used in the SL.